Considerations regarding the emergence and development of patient rights and their application in the pharmaceutical field - Erimia, Cristina-Luiza; Roncea, Florentina-Nicoleta (Technium BioChemMed, 2023)
This paper aims to highlight the historical evolution of the emergence of patient rights, social rights in their essence, as well as their development according to the essential transformations of a society. The present paper aims to show the fact that the patient’s rights were born, first of all, through quantitative assimilations, through increases and overlapping of information from one era to another, they are not the "creation" of contemporary times, the fact that they are based on a certain history written before our eyes. The study of the patient’s rights is intertwined with the study of political concepts, all the more so since the drafting of legislation is directly dependent on political guidelines, and political institutions are directly involved in the legislative act. The development of social relations, their complexity, the unprecedented multiplication of intra- and inter-social contacts, determined a correlative development of law and the emergence of community law, which in the current social reality, represents the positive law applicable on the territory of the European Union.